A preparation method and solar cell based on quasi-two-dimensional perovskite layer
By adding DMSO and MACl in the preparation process of the quasi-two-dimensional perovskite layer and performing auxiliary crystallization, the problem of insufficient stability of perovskite materials is solved, and the preparation of efficient and stable perovskite solar cells is achieved.
Patent Information
- Application Number
- CN202111523090.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-14
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-12-14
AI Technical Summary
Perovskite materials are prone to degradation in oxygen, water vapor, light or high temperature environments, resulting in insufficient stability and limiting their application in the field of solar cells.
By adding DMSO and MACl as additives in the preparation process of the quasi-two-dimensional perovskite layer, and auxiliary crystallization is performed in a constant temperature and heat spin coating machine, the distribution of macromolecules and the crystallization orientation of the film are adjusted to form a dense and stable perovskite layer.
The uniform and dense film formation of the perovskite layer is achieved, which improves its stability and photoelectric properties, and significantly improves the efficiency and long-term stability of quasi-two-dimensional perovskite solar cells.
Smart Images

Figure CN114267796B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a preparation method and a solar cell based on a quasi-two-dimensional perovskite layer. Background Art
[0002] Organic-inorganic hybrid perovskite materials have received extensive attention in recent years as a new type of optoelectronic material. Perovskite materials have high light absorption, large carrier diffusion length and suitable exciton binding energy. In the field of solar cells, the highest efficiency of solar cells based on perovskite materials has exceeded 25%. In the development of perovskite materials, since perovskite materials are sensitive to moisture and oxygen and are easily degraded in oxygen, water vapor, light or high temperature environments, stability is an important factor restricting the development of perovskite materials.
[0003] The existing methods to improve the stability of perovskite materials mainly start from the device structure and encapsulate the perovskite materials. However, the encapsulation process increases the complexity and production cost of device preparation. In recent years, more and more studies have hoped to improve the stability of perovskite materials from the material structure of the perovskite material itself. One of the important solutions is to add organic macromolecules to traditional perovskite materials to convert traditional three-dimensional perovskites into quasi-two-dimensional perovskites. The addition of macromolecules has resulted in the appearance of a macromolecular isolation layer in the quasi-two-dimensional perovskite, which can effectively isolate water vapor and oxygen, greatly improving the water-oxygen stability. However, at the same time, the conductivity of organic macromolecules is poor, which will affect the photoelectric properties of perovskites. With further in-depth research, researchers have found that by optimizing the preparation process of quasi-two-dimensional perovskite films, the distribution of macromolecules in quasi-two-dimensional perovskite films and the crystal orientation of the films can be adjusted. Some commonly used methods, such as additive methods, adding additives such as NH4Cl and MACl to quasi-two-dimensional perovskites, and using a variety of solutions to change the crystallization rate, can effectively control the crystal orientation to a certain extent, and achieve high-performance and high-stability quasi-two-dimensional perovskite solar cells. Summary of the invention
[0004] The purpose of the present invention is to overcome the problems of the prior art and provide a preparation method and a solar cell based on a quasi-two-dimensional perovskite layer.
[0005] In order to achieve the above object, the present invention adopts the following scheme:
[0006] A preparation method based on a quasi-two-dimensional perovskite layer, wherein the main component of the perovskite layer has the molecular formula R 2 A n-1 Pb n I 3n+1 , where n is 5 and R is a macromolecular CH 3 CH 2 CH2 CH 2 NH 3 + Abbreviated as BA, A is CH 3 NH 3 + Abbreviation: MA + ;
[0007] S10 butylamine iodide (BAI), methylamine iodide (MAI) and lead iodide (PbI 2 ) are mixed in a molar ratio of 2:4:5 to obtain a mixture;
[0008] S20: N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) are mixed in a volume ratio of 9:1 or 3:1 to obtain a solvent;
[0009] S30 placing the mixture in the solvent to form a perovskite precursor solution;
[0010] S40 adding 3 mg / ml of MACl to the perovskite precursor solution to obtain a perovskite thin film coating solution;
[0011] S50: spin-coating the perovskite thin film coating solution on the substrate to form a perovskite layer.
[0012] Furthermore, the step S40 further includes adding 3 mg / ml of MACl to the perovskite precursor and stirring the mixture at a constant temperature of 60° C. for 2 hours in a glove box to form a perovskite film coating solution.
[0013] Furthermore, the step S50 further includes:
[0014] The perovskite precursor coating solution is heated to 63° C.;
[0015] The substrate on which the hole transport layer PTAA has been spin-coated is placed on a heating plate of a hot spin coater, wherein the temperature of the heating plate is 60° C.-70° C.;
[0016] After the substrate temperature is stabilized for 5 minutes, the perovskite film coating solution is spin-coated to form a homogenous perovskite film;
[0017] The perovskite film was annealed at 70° C. for 40 min to form a dense and stable perovskite layer.
[0018] A solar cell device, comprising, from bottom to top, the following:
[0019] ITO glass substrate;
[0020] PTAA hole transport layer;
[0021] Perovskite layer;
[0022] C60 electron transport layer;
[0023] BCP isolation layer;
[0024] Silver top electrode.
[0025] Furthermore, the thickness of the ITO glass substrate is 180 nm, the thickness of the PTAA hole transport layer is 10 nm, the thickness of the perovskite layer is 400 nm, the thickness of the C60 electron transport layer is 36 nm, the thickness of the BCP isolation layer is 3 nm, and the thickness of the silver top electrode is 100 nm.
[0026] A solar cell based on a quasi-two-dimensional perovskite layer comprises the following steps:
[0027] S01, cleaning the ITO conductive glass substrate with glass cleaning liquid, acetone and ethanol in sequence, and removing residual organic matter with an ultraviolet ozone cleaning machine after drying;
[0028] S02 PTAA was dissolved in chlorobenzene at a concentration of 2.5 mg / ml, and a PTAA hole transport layer was prepared by spin coating;
[0029] S03 A method for preparing a quasi-two-dimensional perovskite layer to prepare a perovskite layer;
[0030] S04 uses thermal evaporation to deposit the electron transport layer C60 and the isolation layer BCP;
[0031] S05 completes the preparation of the perovskite solar cell by thermally evaporating a silver top electrode on the insulating layer.
[0032] Furthermore, the step S02 further includes placing the PTAA hole transport layer on a hot plate at 100° C. and annealing for 10 minutes.
[0033] Furthermore, in the step S04, the evaporated thickness of the electron transport layer C60 is 36 nm, and the evaporated thickness of the isolation layer BCP is 3 nm.
[0034] Furthermore, the evaporated thickness of the silver top electrode is 100 nm.
[0035] Compared with the existing technology, the present invention has the following advantages: the perovskite layer prepared by the preparation method based on the quasi-two-dimensional perovskite layer is uniform and dense, has excellent stability, and the process method is simple and easy to operate. It can effectively improve the quality of the quasi-two-dimensional perovskite film and regulate the crystal orientation, thereby obtaining a high-performance solar cell device with high operating efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The present application is further described in detail below in conjunction with the accompanying drawings and specific implementation methods.
[0037] Figure 1 It is a schematic diagram of the structure of a solar cell device in the first embodiment of the present invention.
[0038] Figure 2 It is a JV curve diagram of the perovskite solar cells in the embodiment 2 of the present invention and the comparative examples 1, 2 and 3 in actual operation.
[0039] Figure 3 It is a comparison chart of the efficiency of the perovskite solar cells of Example 2 of the present invention and Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4 in actual work.
[0040] Figure 4 This is a diagram showing the stability test results of Example 2 of the present invention. DETAILED DESCRIPTION
[0041] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0042] Based on the research of predecessors, the present invention proposes to use a constant temperature hot spin coater to accurately control the temperature of the substrate, and at the same time add DMSO and MACl to the precursor to assist crystallization, thereby achieving high-quality perovskite film preparation. The structure of the solar cell device prepared by the organic-inorganic hybrid perovskite material of the present invention is as follows Figure 2 As shown, the structure of the solar cell device includes, from bottom to top, a transparent substrate and a first electrode layer 6 , a hole transport layer 5 , a perovskite layer 4 , an electron transport layer 3 , an isolation layer 2 , and a top electrode layer 1 .
[0043] Embodiment 1
[0044] like Figure 1 As shown, in this embodiment, a quasi-two-dimensional organic-inorganic hybrid perovskite material is prepared and a perovskite solar cell is prepared using the material. The transparent substrate of the perovskite solar cell is quartz glass; the first transparent electrode layer is ITO with a thickness of 180nm; the hole transport layer is PTAA with a thickness of 10nm; the main component of the perovskite layer is BA2MA4Pb5I16 with a thickness of 400nm; the electron transport layer is C602 with a thickness of 36nm; the isolation layer is BCP with a thickness of 3nm; the top electrode layer is silver with a thickness of 100nm.
[0045] Embodiment 2
[0046] The preparation steps of perovskite solar cells are as follows:
[0047] The ITO conductive glass was cleaned with glass cleaning liquid, acetone and ethanol in sequence, and after drying, residual organic matter was removed with an ultraviolet ozone cleaning machine.
[0048] PTAA was dissolved in chlorobenzene at a concentration of 2.5 mg / ml, and the PTAA hole transport layer was prepared by spin coating. After spin coating, the sample was placed on a hot stage at 100° C. and annealed for 10 minutes.
[0049] Preparation of perovskite material, i.e., perovskite layer: In a mixed solution of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) with a volume ratio of 9:1 or 3:1 (the total amount of the mixed solution in this embodiment is 2 ml), butylamine iodine (BAI), methylamine iodine (MAI) and lead iodide (PbI2) are added in a molar ratio of 2:4:5 to form a perovskite precursor solution. In this embodiment, the masses of butylamine iodine, methylamine iodine and lead iodide are 128.67 mg, 203.48 mg and 737.61 mg, respectively. 3 mg of MACl is added as an additive, and the mixture is stirred at a constant temperature of 60°C for 2 hours in a glove box to form a yellow uniform perovskite film coating solution. The obtained perovskite film coating solution was heated to 63 degrees, and the ITO conductive glass substrate that had been spin-coated with the hole transport layer PTAA was placed on the heating plate of the hot spin coater. The heating plate was set to 63 degrees. After waiting for 5 minutes, spin coating was started after the temperature of the ITO conductive glass substrate stabilized to form a perovskite film. Annealing was performed at 70 degrees for 40 minutes to obtain a dense and stable perovskite layer.
[0050] The electron transport layer C60 was deposited by thermal evaporation, and the thickness was set to 36 nm. After the evaporation was completed, the isolation layer BCP was deposited, and the thickness was set to 3 nm.
[0051] Finally, a top silver electrode with a thickness of 100 nm was deposited on the insulating layer by thermal evaporation to complete the preparation of the perovskite solar cell.
[0052] Comparative Example 1
[0053] The difference between Comparative Example 1 and Example 2 is that the volume ratio of dimethyl sulfoxide (DMSO) / N,N-dimethylformamide (DMF) in the precursor is 0 and MACl is not added. The remaining steps are exactly the same.
[0054] Comparative Example 2
[0055] The only difference between Comparative Example 2 and Example 2 is that the volume ratio of dimethyl sulfoxide (DMSO) / N,N-dimethylformamide (DMF) in the precursor is 0.03 and MACl is not added.
[0056] The rest of the steps are exactly the same.
[0057] Comparative Example 3
[0058] The only difference between Comparative Example 3 and Example 3 is that the volume ratio of dimethyl sulfoxide (DMSO) / N,N-dimethylformamide (DMF) in the precursor is 0.10, and MACl is not added. The remaining steps are exactly the same.
[0059] Comparative Example 4
[0060] The only difference between Comparative Example 4 and Example 2 is that the volume ratio of dimethyl sulfoxide (DMSO) / N,N-dimethylformamide (DMF) in the precursor is 0.25, and MACl is not added. The remaining steps are exactly the same.
[0061] Comparative Example 5
[0062] The only difference between Comparative Example 5 and Example 2 is that the volume ratio of dimethyl sulfoxide (DMSO) / N,N-dimethylformamide (DMF) in the precursor is 0.50, and MACl is not added. The remaining steps are exactly the same.
[0063] Comparison results between the embodiment and the comparative example: The perovskite thin films and solar cell devices obtained in the embodiment 2 and the comparative examples 1 to 5 were tested. The working conditions were: AM1.5G sunlight (100mW / cm2), temperature 45°C, and nitrogen test environment. Figure 2 The solar cell JV curve test conducted for Example 2 and Comparative Examples 1, 2, and 4 shows that the performance of the example is significantly improved compared to the comparative examples. Figure 3 The efficiency comparison between Example 2 and Comparative Examples 1 to 5 shows that the highest device efficiency of Example 2 reaches 17.66%. Figure 4 This is a stability test of Example 2 in a nitrogen environment. It can be seen that after 1000 hours of storage, its efficiency still maintains more than 95% of the initial efficiency.
[0064] The above is only a preferred implementation of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and substitutions can be made without departing from the technical principles of the present application. These improvements and substitutions should also be regarded as the scope of protection of the present application.
Claims
1. A preparation method based on a quasi-two-dimensional perovskite layer, characterized in that: The main molecular formula of the perovskite layer is R2A n-1 Pb n I 3n+1 , where n is 5 and R is a macromolecule CH3CH2CH2CH2NH3 + Abbreviated as BA, A is CH3NH3 + Abbreviation: MA + ; S10: butylamine iodide (BAI), methylamine iodide (MAI) and lead iodide (PbI2) are mixed in a molar ratio of 2:4:5 to obtain a mixture; S20: N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) are mixed in a volume ratio of 9:1 or 3:1 to obtain a solvent; S30 placing the mixture in the solvent to form a perovskite precursor solution; S40: adding 3 mg / ml MACl to the perovskite precursor solution to obtain a perovskite thin film coating solution; S50: spin coating the perovskite thin film coating solution on a substrate to form a perovskite layer.
2. A preparation method based on a quasi-two-dimensional perovskite layer according to claim 1, characterized in that: The step S40 also includes adding 3 mg / ml of MACl to the perovskite precursor and stirring the mixture at a constant temperature of 60° C. for 2 hours in a glove box to form a perovskite film coating solution.
3. The preparation method based on a quasi-two-dimensional perovskite layer according to claim 1, characterized in that: The step S50 further includes: The perovskite precursor coating solution is heated to 63° C.; The substrate on which the hole transport layer PTAA has been spin-coated is placed on a heating plate of a hot spin coater, wherein the temperature of the heating plate is 60° C.-70° C.; After the substrate temperature is allowed to stabilize for 5 minutes, the perovskite film coating solution is spin-coated to form a homogenous perovskite film; the homogenous perovskite film is annealed at 70° C. for 40 minutes to form a dense and stable perovskite layer.
4. A solar cell device, characterized in that: From bottom to top, there are: ITO glass substrate; PTAA hole transport layer; The perovskite layer according to claim 1; C60 electron transport layer; BCP isolation layer; Silver top electrode.
5. A solar cell device according to claim 4, characterized in that: The thickness of the ITO glass substrate is 180 nm, the thickness of the PTAA hole transport layer is 10 nm, the thickness of the perovskite layer is 400 nm, the thickness of the C60 electron transport layer is 36 nm, the thickness of the BCP isolation layer is 3 nm, and the thickness of the silver top electrode is 100 nm.
6. A solar cell based on a quasi-two-dimensional perovskite layer, characterized in that: The following steps are involved: S01, The ITO conductive glass substrate was cleaned with glass cleaning liquid, acetone and ethanol in sequence; S02 PTAA was dissolved in chlorobenzene at a concentration of 2.5 mg / ml, and a PTAA hole transport layer was prepared by spin coating; S03 prepare the perovskite layer according to the preparation method of claim 1; S04 uses thermal evaporation to deposit the electron transport layer C60 and the isolation layer BCP; S05 completes the preparation of the perovskite solar cell by thermally evaporating a silver top electrode on the insulating layer.
7. A solar cell based on a quasi-two-dimensional perovskite layer according to claim 6, characterized in that: The step S02 further includes placing the PTAA hole transport layer on a hot plate at 100° C. and annealing for 10 minutes.
8. A solar cell based on a quasi-two-dimensional perovskite layer according to claim 6, characterized in that: In the step S04, the evaporated thickness of the electron transport layer C60 is 36 nm, and the evaporated thickness of the isolation layer BCP is 3 nm.
9. A solar cell based on a quasi-two-dimensional perovskite layer according to claim 6, characterized in that: The evaporated thickness of the silver top electrode is 100 nm.
10. A solar cell based on a quasi-two-dimensional perovskite layer according to claim 6, characterized in that: The step S01 also includes removing residual organic matter from the dried ITO conductive glass substrate using an ultraviolet ozone cleaning machine.
Citation Information
Patent Citations
Method for inducing crystallization orientation of perovskite thin film and prepared solar cell
CN108807682A
Preparation method of novel two-dimensional perovskite thin film
CN111244288A